2017
DOI: 10.1126/sciadv.aar3952
|View full text |Cite
|
Sign up to set email alerts
|

In vivo genome editing improves motor function and extends survival in a mouse model of ALS

Abstract: CRISPR-Cas9–mediated genome editing can be used to treat ALS in an animal model of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
120
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 86 publications
5
120
0
1
Order By: Relevance
“…Approximately 20% of familial cases of ALS carry autosomal dominant mutations in the superoxide dismutase 1 (SOD1) gene. The Schaffer group demonstrated that disruption of mutant SOD1 expression in the G93A-SOD1 mouse model of ALS via in vivo CRISPR/Cas9 genome editing using an AAV vector resulted in delayed disease onset, improved motor function, and reduced muscle atrophy (Gaj et al 2017).…”
Section: Mice and Ratsmentioning
confidence: 99%
“…Approximately 20% of familial cases of ALS carry autosomal dominant mutations in the superoxide dismutase 1 (SOD1) gene. The Schaffer group demonstrated that disruption of mutant SOD1 expression in the G93A-SOD1 mouse model of ALS via in vivo CRISPR/Cas9 genome editing using an AAV vector resulted in delayed disease onset, improved motor function, and reduced muscle atrophy (Gaj et al 2017).…”
Section: Mice and Ratsmentioning
confidence: 99%
“…Recently developed nuclease‐based gene‐editing technologies have already breathed new life into somatic gene therapy. CRISPR/Cas9‐based gene editing, with its high efficiency, flexibility, and accuracy, can be applied to correct mutations or inactivate defective exons in animal models or human cells with pathologies such as Duchenne muscular dystrophy (DMD), amyotrophic lateral sclerosis and Huntington's disease . Recently, researchers succeeded in eliminating an entire chromosome in different cell types, including human induced pluripotent stem (iPS) cells with trisomy 21 .…”
Section: Gene Therapy With Somatic Cell Gene Editingmentioning
confidence: 99%
“…4 Recently, the CRISPR-Cas9-mediated allele knock-out genome editing strategy, based on non-homologous end joining (NHEJ) has been successfully applied to correct gain-of-function mutations via AAV. 5, 6, 7, 8 One of the unique advantages of the genome editing approach is that it allows local treatment of the genome, such that the approach does not depend on the size of the target gene. However, genome editing for loss-of-function mutations in larger genes that require local replacement of the mutated sequence with a wildtype counterpart (mutation replacement) has not been successful in treatment of neuronal disorders primarily affecting neurons, due to its low editing efficiency.…”
Section: Introductionmentioning
confidence: 99%